ANALYSIS OF CHATBOOT APPLICATIONS IN SERVICES OUTPUT TREATMENT WITH THE TAM MODEL APPROACH: ANALISIS APLIKASI CHATBOOT DALAM PELAYANAN BEROBAT JALAN DENGAN PENDEKATAN TAM MODEL - Surya Ade Saputera; Yuyun Afrika Sari (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
In outpatient services, there are limited resources such as medical personnel, waiting time, and limited physical space. Using a chatbot application can help overcome limitations by providing faster and more efficient access for patients to obtain medical information and consultations. The purpose of this study is to analyze user perceptions of the use of the chatbot application in outpatient services using the TAM Model. The research method in this study was a survey method. The population in this study were outpatient patients. The analytical method used is multiple linear regression analysis, T-test and F-test. The results of the research variable Perceived Usefulness has no effect on Attitude Towards Using users in using the chatboot application in outpatient services with a significance level of 0.324 > Î± (0.05). Perceived Ease of Use affects the Attitude Towards Using of users in using the chatboot application in outpatient services with a significance level of 0.001 < Î± (0.05). Perceived Usefulness and Perceived Ease of Use together influence the Attitude Towards Using of users in using the chatboot application in outpatient services. Keywords: Perceived Usefulness, Perceived Ease of Use, Attitude Towards Using, Chatbot, TAM Model